(untitled) (Filološke studije, 2019)
In this article I will be dealing with a specific type of banishment (escape, to be more precise), inspired by a subtle condition of the spirit wich Gilles Deleuze defined as ’psychic nomadism’, and Hakim Bey mockingly termed ’cosmopolitisam without roots’. Both terms are related to the homonym ’no man’s land’, in wich Jean-François Lyotard recognized the secret area of our escape, where we go frim time to time, although some of us prefer to do it very often. It is by no means a geopolitical phenomenon (as a matter of fact, I have no intentions of adding political connotations to my exposé), although it is obvious that the three terms are united under a common denominator which is manifested as a resistance toward the institutions of the system.